Comparison of multi‐ and single‐frequency bioelectrical impedance analysis with dual‐energy X‐ray absorptiometry for assessment of body composition in post‐menopausal women: effects of body mass index and accelerometer‐determined physical activity. Issue 4 (7th July 2014) - Gába, A.; Kapuš, O.; Cuberek, R.; Botek, M.
Abstract Background Bioelectric impedance analysis (BIA) is commonly used in research to assess body composition. However, studies that validate the accuracy of BIA exclusively in post‐menopausal women are lacking. The main purpose of the present study was to evaluate the agreement of multi‐frequency (MF)‐BIA and single‐frequency (SF)‐BIA with dual‐energy X‐ray absorptiometry (DXA) in the estimation of fat mass (FM) and fat‐free mass (FFM) among post‐menopausal women with variation in body mass index (BMI) and physical activity (PA). Methods FM and FFM were estimated by BIA and DXA in 146 post‐menopausal women with a mean (SD) age of 62.8 (5.2) years. PA was determined by an accelerometer. Results The mean (SD) difference between MF‐BIA and DXA was −1.8 (1.8) kg (P = 0.08) and 1.3 (1.8) kg (P = 0.01) for FM and FFM, respectively. SF‐BIA provided a significantly lower estimate of FM [−2.0 (2.2) kg; P = 0.04] and a higher estimate of FFM [1.8 (2.4) kg; P < 0.01] compared to DXA. MF‐BIA provided significantly better estimates of FM and FFM with narrower limits of agreement than SF‐BIA in obese and insufficiently active subjects. In other BMI and PA groups, both BIA devices showed a similar deviation from DXA. Conclusions BIA tends to underestimate FM and overestimate FFM relative to DXA. MF‐BIA appears to be a more appropriate method for the assessment of body composition than SF‐BIA in post‐menopausal woman with BMI >30 kg/m2 and in those who are insufficiently active.